Structural carbon-carbon materials for accelerator-driven systems - Gurin, V.A.; Bakai, A.S.; Gurin, I.V.; Omelchuk, A.A.; Buryak, M.I.; Voronin, B.M.; Shmehera, R.S. (Вопросы атомной науки и техники, 2005)
The paper presents results of investigations of the compatibility of carbon-carbon composite materials with molten sodium fluoride – zirconium fluoride mixture in the presence of molten lead and its fluoride. The investigations have been carried out both without irradiation and with irradiation with an electron beam of 10 MeV energy and 5 kW power (current density 0.5 mA/cm2) on a linear electron accelerator LPE–10 (LINAC–10). It has been shown that this material is impermeable to the above compounds. Does not interact with them. And does not break down on temperature cycling from room temperature to 700 °C. The mechanical properties of carbon-carbon composites have been investigated by the nanoindentation method. It has been found that neither long contact with molten fluoride mixture nor irradiation affects the mechanical properties of this material.